“Adults with congenital heart defects”: current challenges in medical care. Part II: infective endocarditis, pulmonary hypertension, aortopathy, cardiac surgical aspects, psychocardiology, unresolved problems and future aspects: Position paper of the German Cardiac Society „Erwachsene mit angeborenen Herzfehlern“: Aktuelle Herausforderung in der medizinischen Versorgung Teil II: Infektiöse Endokarditis, pulmonale Hypertonie, Aortopathien, herzchirurgische Aspekte, Psychokardiologie, ungelöste Probleme und Zukunftsaspekte: Positionspapier der Deutschen Gesellschaft für Kardiologie - Kaemmerer, Harald; Baldus, Stephan; Baumgartner, Helmut; Berger, Felix; de Haan, Fokko; Frantz, Stefan; Loßnitzer, Dirk; Uebing, Anselm; Lebherz, Corinna; Weyand, Michael; Diller, Gerhard Paul (Die Kardiologie, 2023)
Despite relevant residual and sequelae, follow-up of adults with congenital heart defects (ACHD) is too often not provided by/at specialized and/or certified physicians or medical centers, even though significant problems may develop in the long-term course. In addition to specific CHD related residua, heart failure and arrhythmias, major problem constellations include infective endocarditis, pulmonary vascular disease, and pulmonary hypertension and aortopathy. In addition, there are cardiac and noncardiac comorbidities, including psychological burdens. This position paper of the German Cardiac Society provides up to date information on these problems and emphasizes the urgent need for experienced follow-up by specialized physicians or hospitals, as treatment regimens of acquired heart disease cannot entirely be transferred to CHD. In addition, the need for primary and secondary medical prevention is emphasized to reduce the burden of disease as well as the socioeconomic burden and costs in this particular patient population.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Adult; Aortopathies; Cardiac surgery; Congenital heart disease; Follow-up; Infective endocarditis; Psychocardiology; Pulmonary hypertension